The Use of Generative Artificial Intelligence in Public Relations Practice in Indonesia: A Systematic Literature Review - NISRINA NABILA (Jurnal Komunikasi, Masyarakat dan Keamanan, 2026)
The development of digital technology has encouraged the use of generative artificial intelligence (AI) in various organizational communication practices, including in the field of Public Relations (PR). Generative AI technology, such as ChatGPT, is used as a supporting tool in digital communication management, content production, and public information services. Although its use in public relations practices is becoming more widespread, studies on generative AI in the context of Public Relations in Indonesia are still fragmented and have not been analyzed systematically. This study aims to systematically examine the use of generative AI in Public Relations practices in Indonesia through a Systematic Literature Review (SLR) approach. This study analyzes national scientific articles published between 2019 and 2025 by grouping research findings into main themes, including the use of AI in organizational communication, the role of AI in supporting public relations functions, and the accompanying ethical issues and professional challenges. The results of the study show that generative AI is mainly used to improve the efficiency of digital communication management, maintain message consistency, and accelerate the organization's response to the public. However, most of the literature emphasizes that generative AI does not replace the strategic role of Public Relations practitioners. In addition, communication ethics issues, such as transparency, accountability, and human supervision, are a major concern in the use of generative AI. This study concludes that generative AI serves as a strategic support tool in Public Relations practice when used responsibly and integrated with human communication competencies. Keywords: generative artificial intelligence; public relations; digital communication; ChatGPT; systematic literature review